2021
DOI: 10.3390/ijerph182412902
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge into the Practice against COVID-19: A Cross-Sectional Study from Ghana

Abstract: The COVID-19 pandemic has affected populations globally, including Ghana. Knowledge of the COVID-19 disease, and the application of preventive public health interventions are pivotal to its control. Besides a lockdown, measures taken against the spread of the virus include the wearing of face masks, social distancing, regular hand washing with soap and, more recently, vaccination against the virus. In order to establish a possible link between the knowledge of the disease and compliance with preventive measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In line with their healthy lifestyle behavior, 70% of them had high to very high compliance with COVID-19 infection prevention strategies, while 24.7% reported medium commitment. This is similar to the previous research conducted early in the pandemic, that reported high compliance levels with preventive measures and high willingness to self-isolate, while other studies in other settings showed poor compliance with those prevention measures and low levels of vaccinations acceptance at the same time [36] , [37] , [38] , [39] .…”
Section: Discussionsupporting
confidence: 90%
“…In line with their healthy lifestyle behavior, 70% of them had high to very high compliance with COVID-19 infection prevention strategies, while 24.7% reported medium commitment. This is similar to the previous research conducted early in the pandemic, that reported high compliance levels with preventive measures and high willingness to self-isolate, while other studies in other settings showed poor compliance with those prevention measures and low levels of vaccinations acceptance at the same time [36] , [37] , [38] , [39] .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the statistic revealed by the participants (50.5%) is significantly lower than the United Kingdom (83.1%) (Gohel, Patel, Shah, Patel, Pandit & Raut, 2021), United States (92%) (Geldsetzer, 2020); Saudi Arabia (81.6%) (Al-Hanawi, Angawi, Alshareef, Qattan, Helmy et al, 2020); Developed countries (78.3) (Adefisoye, Adefisoye, George & Bisi-Johnson, 2021); Ghana (69.9) (Yeboah, Daliri, Abdin, Appiah-Brempong, Pitsch et al, 2021), similar to Bangladesh (Islam, Siddique, Akter, Tasnim, Sujan, Ward & Skder, 2021); Developing countries (59.5%) (Adefisoye, Adefisoye, George & Bisi-Johnson, 2021); West Africa (67.8%) (Udoakang, Zune, Tapela, Owoicho, Fagbohun et al, 2022); Malaysia (62%) (Mohamad et al, 2021); Ethiopia (46.9) (Adane, Ademas & Kloos, 2022). The findings compare pointedly with Wallis (2020) who argues the inclination to shun vaccination is endemic when a novel pandemic strikes, particularly due to the dearth of information about the risk inherent in vaccines.…”
Section: Discussion Of Findingsmentioning
confidence: 59%
“…In Ethiopia, the highest acceptance was 97.9% 25 and the lowest, 45.5% 31 . In Ghana, acceptance ranged from 64.72% 32 to 35% 33 . In Libya, acceptance ranged from 79.6% to 41.2%, depending on the vaccine efficacy 34 .…”
Section: Resultsmentioning
confidence: 99%